Moral sentiment and reason: The notion of justice in Adam Smith and Amartya Sen (2014)
Amartya Sen argues that his notion of justice has its origins in the thinking of Adam Smith. Sen employed, in a very particular way, the concepts of sympathy and the impartial spectator. Beyond the statement of Sen, we are interested in researching whether Smith's notion of justice is compatible with Sen's. The main finding is that there are significant differences between the theories and therefore they are not compatible. Smith emphasized the importance of moral judgment based on sentiment. Conversely Amartya Sen emphasizes the need to use reason and public debate as key elements of a theory of justice.